Sodium Fluoride Administration Enhances Osteocalcin and Osteonectin Expression in Alveolar Bone on the Tension Side on Orthodontic Tooth Movement - Rina Sutjiati; Rudy Joelijanto; Devina Yulia; Anjelia Gelli (Humanistic Network for Science and Technology (HNST), 2021)
Introduction: In the tension side on the orthodontic tooth movement, the bone formation process occurs, played by osteoblasts. Bone formation by osteoblasts in vitro can be increased by administering NaF (sodium fluoride). Speed of bone formation is one of the most important steps in orthodontic tooth movement. Objectives: to analize the effect of NaF administration on the expression of osteocalcin and osteonectin in the strain area in the incisors after orthodontic tooth movement. Methods: The 10 Wistar adult male rats were given 10 grams of orthodontic mechanical strength on the incisors so that the incisors moved distally and were given NaF twice a day, compared to 10 mice in the control group with the same treatment without NaF administration. Results: NaF increase osteocalcin expression by 31.1% on day 7 and 44.8% on day 14, whereas in osteonectin the increase is 48.1% on day 7 and 26.2% on day 14. Conclusions: NaF increases the expression of osteonectin and osteocalcin in mice that were given orthodontic mechanical strength. Keywords: sodium fluoride; immunohistochemistry; osteocalcin; osteonectin